Physical exercise during exposure to 40-Hz light flicker improves cognitive functions in the 3xTg mouse model of Alzheimer’s disease - Sang-Seo Park (Alzheimer’s Research & Therapy, 2020)
Abstract Background Exercise promotes brain health and improves cognitive functioning in the elderly, while 40-Hz light flickering through the visual cortex reduces amyloid beta (Aβ) by stabilizing gamma oscillation. We examined whether exercise was associated with hippocampus-mediated improvement in cognitive functioning in the 3xTg-Alzheimer’s disease (3xTg-AD) murine model following exposure to 40-Hz light flickering and exercise. Methods We subjected 12-month-old 3xTg-AD mice to exercise and 40-Hz light flickering for 3 months to investigate spatial learning, memory, long-term memory, Aβ levels, tau levels, mitochondrial functioning including Ca2+ retention and H2O2 emission, apoptosis, and neurogenesis in the hippocampus. Results Treatments had a positive effect; however, the combination of exercise and 40-Hz light flickering exposure was most effective in reducing Aβ and tau levels. Reducing Aβ and tau levels by combination of exercise and 40-Hz light flickering improves Ca2+ homeostasis and reactive oxygen species such as H2O2 in mitochondria and apoptosis including bax, bcl-2, cytochrome c, and cleaved caspase-3 and cell death, cell differentiation, and neurogenesis in the 3xTg-AD model of the hippocampus, resulting in improving cognitive impairment such as spatial learning, memory and long term memory. Conclusion Our results show that exercising in a 40-Hz light flickering environment may improve cognitive functioning by reducing Aβ and tau levels, thereby enhancing mitochondrial function and neuroplasticity.